Tożsamość i autobiografia - Lubas-Bartoszyńska, Regina (Przestrzenie Teorii, 2007)
Identity as an omnipresent category in science, art and life is considered by the author in reference to man. The author is mainly interested in an individual identity as revealed in writing. It is most fully revealed in autobiographical writing. Considerations on the subject of autobiographical identity are preceded by a reflection on the identity of existence as contained in philosophy already since the times of Hume, in the writings of theologists and in essayist discourses. Roughly speaking, two conceptions are outlined in the writings of an autobiographical character, especially the ones which belong to the Franconian culture.